2021
DOI: 10.1007/s00787-021-01858-8
|View full text |Cite
|
Sign up to set email alerts
|

Preventing suicide in post-secondary students: a scoping review of suicide prevention programs

Abstract: Suicide among students enrolled in post-secondary education, including university or college, is a major public health concern. Previous research has examined the effectiveness of suicide prevention programs for this population. However, the effective elements of these interventions remain unknown. This study reviewed the literature on suicide prevention programs for post-secondary students, exploring and identifying those elements likely contributing to their effectiveness. A scoping review process was undert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 47 publications
(101 reference statements)
0
18
0
Order By: Relevance
“…This review follows the enhanced framework of scoping reviews23 that builds on the originally proposed methodology of Arksey and O’Malley 24. The framework incorporates six stages, each of which are detailed in the subsequent sections1: identifying the research question,2 identifying relevant studies,3 selecting studies,4 mapping/charting the data,5 collating, summarising, reporting the results and6 expert consultation. The reporting of the review will follow the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Extension for Scoping Reviews (PRISMA-ScR) 25…”
Section: Study Rationalementioning
confidence: 99%
See 2 more Smart Citations
“…This review follows the enhanced framework of scoping reviews23 that builds on the originally proposed methodology of Arksey and O’Malley 24. The framework incorporates six stages, each of which are detailed in the subsequent sections1: identifying the research question,2 identifying relevant studies,3 selecting studies,4 mapping/charting the data,5 collating, summarising, reporting the results and6 expert consultation. The reporting of the review will follow the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Extension for Scoping Reviews (PRISMA-ScR) 25…”
Section: Study Rationalementioning
confidence: 99%
“…3 Data such as this highlights the importance of suicide prevention for this group and existing evidence suggests that postsecondary education is a setting where suicide prevention programmes can be delivered effectively. [4][5][6] However, some groups may face a unique combination of risk factors and barriers that heighten the risk of suicide, 7 8 requiring tailored suicide prevention strategies if interventions are to be effective. 9 Postsecondary international students, referred to as international students for the remainder of this protocol, are such a group and make up a significant proportion of the student body in many countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a literature review exploring Suicide prevention programs targeting tertiary students [ 17 ] highlighted that the majority of programs were directed at gatekeepers rather than tertiary students themselves and delivered almost exclusively face-to-face. While overall findings across studies indicated that these training programs might effectively improve mental health knowledge and attitudes, student outcomes were rarely measured.…”
Section: Introductionmentioning
confidence: 99%
“…While overall findings across studies indicated that these training programs might effectively improve mental health knowledge and attitudes, student outcomes were rarely measured. Therefore, little is known of the role of prevention programs in impacting student engagement with services, their suicidal ideation or broader mental health outcomes [ 17 ]. While increasingly tertiary education is delivered via virtual means, pointing to an opportunity for delivering suicide programs online [ 18 ], to date, only one such program has evaluated tertiary students increased knowledge of prevention strategies two months post completion of the program [ 19 , 20 ], with the application of this knowledge in real-life situations remaining unknown.…”
Section: Introductionmentioning
confidence: 99%